The The Influence of Organizational Culture and Leadership Style on Employee Performance Mediated by Employee Competence at PT. East Makassar - Irwan, Irwan; Idris, Rabiatun; Fajriah, Yana; Wahyuningsih, Sri (Gema Wiralodra, 2024)
This research aims to determine the direct influence of organizational culture variables, leadership style and employee competency on employee performance and the indirect influence of organizational culture variables and leadership style on employee performance with employee competency as mediation at PT. East Makassar. Primary data were obtained using a questionnaire with a saturated sample. The population was 43 respondents. The questionnaire was tested for validity and reliability with the PLS model scheme and model evaluation, as well as multicollinearity tests, inner model evaluations using the determinant coefficient test, goodness of fit model tests and hypothesis testing both directly and indirectly were carried out using the SmartPLS version 4 application. The results of the study directly showed that organizational culture variables have a positive and significant effect on employee performance, leadership style variables have no effect on employee performance, organizational culture variables have a positive and significant effect on employee competence, leadership style variables have no effect on employee competence and employee competence has a positive effect significant impact on employee performance. The research results indirectly show that organizational culture influences employee performance with employee competency as a mediator and leadership style does not influence employee performance with employee competency as a mediator.